Development of a water level monitoring and control system for pumping stations in agricultural systems - Iug Lopes; Jhuliana Mércia Assis Nascimento; Rafael Souza Barbosa; Marcelo Rocha dos Santos; Rafael Dias Heydt; Elias Guimarães Miranda Barbosa da Silva; Juliana Maria Medrado de Melo; Lucas Melo Vellame; JJoão Luis Mendes Pedroso de Lima; Miguel Julio Machado Guimarães (Dyna)
Monitoring water levels in reservoirs and suction pipes is essential to avoid failures in pumping and agricultural systems. This study aimed to develop an intelligent system for automated monitoring of water levels in irrigated agricultural reservoirs, ensuring safer operation of pumping stations and aiding decision-making. The system enables visualization, water level management, and protection of motor pumps. After assembly and programming, the prototype was installed in a reservoir. Tests showed a difference of less than 5 mm between manual and system measurements. Google Sheets was used for accurate data analysis. The control system includes a contactor, thermal relay, bipolar circuit breaker, simple control relay (activated by the ESP32), and two buttons — one normally closed and one normally open. The proposed intelligent system proved effective for automated water level management in reservoirs.